Nuclear Changes Features in Buccal Mucosa Smear of Adult Male Smokers Using Pappaniculou Staining - Kharisma, Yuktiana; Indriyanti, Raden Anita; Yuniarti, Lelly; Noormartany, Noormartany; Nur, Ismet Muchtar; Yenolinsky, Yolanda (Althea Medical Journal, 2025)
Background: Tobacco smoke contains a combination of chemicals that could be harmful to the buccal mucosa as the first part of the body that has been exposed. Damage to the buccal epithelial cells has the potential to become a malignant lesion. This study aimed to describe changes in the nuclear epithelial of the buccal mucosa using Pappaniculou staining as an indicator of mucosal damage in smokers.Methods: This was a descriptive analytical study, involving adult male participants from Bale Endah District, Bandung Regency, Indonesia aged >35 years, who had smoked for ≥10 years. Buccal mucosa smear was taken, and the features of nuclear epithelial changes were observed per 500 cells, each at 400x magnification with Pappaniculou stain to evaluate the features of micronucleus, broken egg, karyorrhexis, karyolysis. Those who did not smoke were recruited as a control group.Results: Smokers were mostly light active smokers or kretek cigarettes, with a smoking duration of ≥15 years. The frequency of micronucleus (p<0.001), broken eggs (p<0.001), karyorrhexis (p=0.001), karyolysis (p=0.003) in the buccal mucosal epithelial was significantly different between the smoker and non-smoker groups.Conclusions: All epithelial nuclear changes have shown significant differences between smoker and non-smoker groups. Nuclear epithelial features in smoker may be associated with future malignancies, therefore, smoking cessation programs are necessary to substantially reduce tobacco use, thus fostering a healthy lifestyle for everyone.